Protective Effect of Ethanol Extract Tempuyung Leaf (Sonchus arvensis L.) Against Gentamicin Induced Renal Injury Viewed from Blood Ureum Level - Imelda, Imelda; Azaria, Cherry; Lucretia, Teresa (Maranatha Christian University, 2017)
Acute renal injury is characterized by decrement of glomerular filtration rate (GFR), resulting in nitrogen metabolic end product retention such as blood ureum. Aminoglycoside nephrotoxic injuries are common in elderly, with mortality rate 50-70%. Tempuyung has been empirically used in relieving renal problems as it contains several active antioxidants. This study aimed to analyze the protective effect of ethanol extract tempuyung leaf (EET) against gentamicin induced renal injury viewed from blood ureum level. The method used was true experimental laboratory, 16 wistar male rats, divided into 4 groups (n=4): negative control group (CMC), positive control group (Gentamicin 80 mg/kgBW), 1st treatment group (EET 100 mg/kgBW + Gentamicin), 2nd treatment group (EET 200 mg/kgBW + Gentamicin) for ten days. On the 11th day, blood serum were taken and the ureum level were analyzed. Data was analyzed by ANOVA and post hoc LSD test. Result showed positive control group had the highest blood ureum level (29.50 ï± 1.29 mg/dL) compared to negative control group (14.25 ï± 1.26 mg/dL), 1st treatment group (26.50 ï± 0.58 mg/dL), and 2nd treatment group (22.25 ï± 1.26 mg/dL) with significance difference (p<0,001). In conclusion, the result suggested the protective effect of EET against gentamicin induced renal injury.Keywords: acute renal injury, gentamicin, glomerular filtration rate, tempuyung, ureum